Os desafios e possibilidades da organização e funcionamento do regime semiaberto harmonizado com monitoração eletrônica no município de Ponta Grossa – PR - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2023)
The research in question aims to understand the challenges and potentialities of the organization and operation of penal execution in the semi-open regime harmonized with electronic monitoring in Ponta Grossa, based on its administrative, institutional, and management elements. The research is defined as descriptive-exploratory, of a qualitative nature, absorbing in its methodological course techniques of bibliographic and documentary surveys, as well as semi-structured interviews, which were conducted with the technical team of the Nucleus for Assistance to individuals under electronic monitoring (NUPEM). The collected data were analyzed using the content analysis technique. As a result, the design of the organization and implementation of the electronic monitoring policy in the municipality is visualized, along with the diversity of understanding regarding the challenges in this process and the uniformity of workers' understanding regarding potentialities to be explored by the institution. With these findings, the intention is to enhance and provide a broader theoretical, analytical, and operational scope for the discussion on the topic in the municipality.
Keywords: Monitoração eletrônica; Execução penal; Semiaberto harmonizado; Potencialidades; Desafios; Electronic monitoring; Penal execution; Harmonized semi-open; Potentialities; Challenges; CNPQ::CIENCIAS SOCIAIS APLICADAS